Hydrogel Containing Anti-CD44-Labeled Microparticles, Guide Bone Tissue Formation in Osteochondral Defects in Rabbits - Filová, Eva; Tonar, Zbyněk; Lukášová, Věra; Buzgo, Matěj; Litvinec, Andrej; Rampichová, Michala; Beznoska, Jiří; Plencner, Martin; Staffa, Andrea; Daňková, Jana; Soural, Miroslav; Chvojka, Jiří; et al. (Nanomaterials (Basel, Switzerland), 2020)
Hydrogels are suitable for osteochondral defect regeneration as they mimic the viscoelastic environment of cartilage. However, their biomechanical properties are not sufficient to withstand high mechanical forces. Therefore, we have prepared electrospun poly-ε-caprolactone-chitosan (PCL-chit) and poly(ethylene oxide)-chitosan (PEO-chit) nanofibers, and FTIR analysis confirmed successful blending of chitosan with other polymers. The biocompatibility of PCL-chit and PEO-chit scaffolds was tested; fibrochondrocytes and chondrocytes seeded on PCL-chit showed superior metabolic activity. The PCL-chit nanofibers were cryogenically grinded into microparticles (mean size of about 500 µm) and further modified by polyethylene glycol-biotin in order to bind the anti-CD44 antibody, a glycoprotein interacting with hyaluronic acid (PCL-chit-PEGb-antiCD44). The PCL-chit or PCL-chit-PEGb-antiCD44 microparticles were mixed with a composite gel (collagen/fibrin/platelet rich plasma) to improve its biomechanical properties. The storage modulus was higher in the composite gel with microparticles compared to fibrin. The Eloss of the composite gel and fibrin was higher than that of the composite gel with microparticles. The composite gel either with or without microparticles was further tested in vivo in a model of osteochondral defects in rabbits. PCL-chit-PEGb-antiCD44 significantly enhanced osteogenic regeneration, mainly by desmogenous ossification, but decreased chondrogenic differentiation in the defects. PCL-chit-PEGb showed a more homogeneous distribution of hyaline cartilage and enhanced hyaline cartilage differentiation.
Keywords: cartilage; collagen; microparticles; fibrin; CD44 antibody; poly-ε-caprolactone